Comparative study of floral biology using detergent and confirm selfincompatibility system in protogynous lines of Indian mustard (Brassica juncea) - CHANDU SINGH; BORAIAH K M; RAJIV K SINGH; S P JEEVAN KUMAR; GYANENDRA SINGH; RAMESH CHAND (The Indian Journal of Agricultural Sciences, 2018)
Seven genotypes of mustard [Brassica juncea (L.) Czernj and Coss.], protogynous lines (F3-5 generation), cytoplasmic male sterility (CMS) line and different concentrations (3, 5 and 8% (w/v)) of detergent (synthetic detergent powder was used in present investigation. There is effect of detergent which induces more prominent male sterility expression in Pusa Bold followed by Ashirwad genotypes and more vigorous during floral bud initiation, resist to scorching effect and delayed in flowering. Furthermore, the floral attributes, viz. anther length (mm), no. of pollen grains/bagged flower, pollen fertility, stylar length (mm), stigma receptivity, no. of ovules and seed set (%) were highly significant and which induced 100 % male sterility. Similarly, the pollen-ovule ratio was found to be nonsignificant and the yield0/plant significantly declined with increase in detergent concentration. The PG line showed more prominent stigma exertion, extended protogynous interval (9-10 days) and stigma receptivity (3-4 days) from its protrusion compared to induced male sterile line. The expression of male sterility in PG and CMS lines showed the partial sterility (30-50%) and absolute (100%) respectively. Further, the PG line had low seed set on selfing even it produces normal pollen (pollen viability test) but it was high seed setting occurs with out-crossing hence, it was confirmed presence of self- incompatibility system in the protogynous plants.